The Influence of Hiv Knowledge on Prevention Practices Among Female Youth Aged 15-24 Years in Kisumu East Sub- County, Kenya. - Odero, Tabitha Adhiambo (Amref International University, 2025)
Introduction: Approximately 39 million people globally live with HIV/AIDS, women and girls accounting for 54% of infections. Kisumu County in Kenya has a HIV prevalence 3.5 times the national average. In 2022, it ranked 4th nationally for new infections among 15-24-year-olds, with HIV prevalence rates 1.2 times higher in females. By 2019, HIV-related mortality in Kisumu County was over 20% higher among females than males. Comprehensive HIV knowledge in young women remains low, averaging 38.5% in sub-Saharan Africa and 33.8% in Kenya, especially in Kisumu’s rural and informal areas. The objective was to assess HIV knowledge and its impact on prevention practices among females aged 15-24 in Kisumu County. Methods: A Cross-sectional study on 429 respondents selected by two stage cluster sampling from the 5 wards in Kisumu East Sub County. Data collection using structured questionnaires, key informant guides and recorders for in-depth interviews. Data analysis using R (version >= 4.3.1) for quantitative data and thematic analysis for qualitative data. Results: School was the main HIV knowledge source, with 85% showing high knowledge – especially older educated respondents. Sexual debut averaged 17 years with low condom use and limited testing among younger respondents. Higher HIV knowledge was linked to 51% and 72% lower abstinence odds (aOR=0.49, 0.28). Despite a positive trend in condom use, consistent use was lower in the high knowledge group (aOR=0.32). High knowledge increased awareness of personal (aOR=3.87) and partner HIV status (aOR=6.82), PEP/PrEP (aOR=4.24) and reduced high-risk behavior (aOR=0.47) but was not linked to age at sexual debut or monogamy. Conclusion: HIV prevention programs must go beyond disseminating information to include peer education and behavioral support, to enhance the practical application of knowledge and reduce infection rates.
A Research Thesis Submitted to The Department of Community Health, School of Public Health in Partial Fulfilment of The Requirements for A Master of Public Health Degree of Amref International University